1998
DOI: 10.1097/00004647-199802000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Ischemic Brain Injury in Interleukin-1β Converting Enzyme—Deficient Mice

Abstract: Both of these markers of brain injury were significantly re-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
157
1
4

Year Published

1998
1998
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 298 publications
(165 citation statements)
references
References 42 publications
3
157
1
4
Order By: Relevance
“…Published data have shown a linear relationship between CBF reduction and MCAO as measured by simultaneous LDF or 14C-IMP. 47,48 We expressed the changes of CBF as a percentage by setting the baseline value as reference group for consistent measurement comparison at different time points. We found that AAVH9-VEGF improved CBF recovery in the perifocal cortex starting at 1 week of tMCAO, and that further recovery extended to the core area 2 weeks of tMCAO.…”
Section: Aavh9-vegf Promotes Angiogenesismentioning
confidence: 99%
“…Published data have shown a linear relationship between CBF reduction and MCAO as measured by simultaneous LDF or 14C-IMP. 47,48 We expressed the changes of CBF as a percentage by setting the baseline value as reference group for consistent measurement comparison at different time points. We found that AAVH9-VEGF improved CBF recovery in the perifocal cortex starting at 1 week of tMCAO, and that further recovery extended to the core area 2 weeks of tMCAO.…”
Section: Aavh9-vegf Promotes Angiogenesismentioning
confidence: 99%
“…Early evidence that caspase-1 plays a role in neuronal cell death came from the findings that caspase-1-deficient neurons showed prolonged survival following trophic factor withdrawal-induced apoptosis. 69,70 Similarly, neuronal overexpression of a dominant negative and catalytically inactive (C 285 G) caspase-1 in mice resulted in an increase in resistance to neurotoxicity. 71 So far, there does not appear to be a common event responsible for inducing caspase-1 activation in neurodegenerative diseases.…”
Section: 12mentioning
confidence: 99%
“…Indeed, Caspase-3 activation contributes to brain tissue loss and downstream biochemical events leading to programmed cell death after traumatic brain injury (3,4). Both genetic disruption and pharmacological inhibition of caspases after stroke can reduce ischemic neuronal injury inducing a neuroprotective effect (5)(6)(7)(8). It has been suggested that silencing of apoptotic genes using in vivo RNA interference (RNAi) could be potentially an effective treatment for stroke (5,9) .…”
mentioning
confidence: 99%